France Prešeren in František Ladislav Čelakovský - znaki, razmerja in pomeni - Vinkler, Jonatan (Jezik in slovstvo, 1999)
The article discusses František Ladislav Čelakovský's contacts with France Prešeren and the influence of his aesthetics on Prešeren's creative paradigm, and through it on the development of Slovene literature.
Keywords: Prešeren, France, 1800-1849; Čelakovský, František Ladislav, 1799-1852; Slovene literature; slovenska književnost; slovenska literarna zgodovina; literarni zgodovinarji; literary historian; 19.st.